ON THE PRECIPITATION HOMOGENEITY HYPOTHESIS IN TOPMODEL APPLICATIONS - Karam, Hugo Abi; Pereira Filho, Augusto José; Flores Rojas, José Luis (Revista Brasileira de Cartografia, 2017)
The objective of this work is to analyze the asymptotic conditions of similarity of soil water distribution over complex terrain and propose a relaxation of the rainfall spatial homogeneity, which is considered in the hydrological distribution TOPMODEL. The result is a generalization based on the conservation of material properties over the asymptotic drain paths of the complex terrain. The similarity hydrological conditions are here considered to be weak restrictions on the variational problem. In practice, a numerical application was built to assist weather forecasters in the diagnosis and prognosis of hydrometeorological conditions of increased risk, such as landslides and ï¬‚ ash ï¬‚ oods. These events can occur in much smaller time scales that provided by the usual weather forecasts in the synoptic scale.